The longest strongest thread - Leiṭner, ʿInbal (Scallywag Press Ltd, 2020)
"We are moving to a new home, where the lakes freeze in winter. I am visiting my Grandma to say goodbye." The little girl in this story is moving with her parents to a new, colder country very far away. She loves visiting her Grandma's sewing studio and watching her make things and is worried about leaving Grandma behind. As the girl makes a toy aeroplane and a map so that her Grandma can come and visit her in the new country, Grandma is busy making a coat to keep her Grandchild warm. Grandma says I mustn't worry that my new home is so very far away. She says that we two have the longest, strongest thread in the whole world, and she will surely fly all the way to find me